Educating Freedom: The Beauty of a Task - Barraca Mairal, Javier (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2020)
This paper reflects on the relationships between education and human freedom. Firstly, it is pointed out that-due to the reality of personal beings, their uniqueness and originality-freedom constitutes an essential basis of the educational task. it is also claimed that the development of freedom within education demands to be considered as a horizon and as a path at the same time. to this end, this paper critically delves into issues such as the notion of human freedom, its types, its main features and meaning and its connection to values.